Optimization of Processing Parameters for Lettuce Vacuum Osmotic Dehydration Using Response Surface Methodology - Yuan Yuejin; Tan Libin; Xu Yingying; Dong Jixian; Zhao Yu; Yuan Yueding (Polish Journal of Food and Nutrition Sciences)
In order to obtain the optimal technological parameters of lettuce vacuum osmotic dehydration, the effects of osmotic temperature, slice thickness, sucrose concentration, and vacuum degree on the vacuum osmotic dehydration were explored. The lettuce water loss rate and solid gain rate decreased with the increase of slice thickness and vacuum degree, and increased with the increase of sucrose concentration and osmotic temperature. Response surface methodology was applied to analyze the influence of the four influential factors on the evaluated parameters and the optimization of lettuce vacuum osmotic dehydration was studied. The results indicated that, within the experimental scope, the optimized technological parameters of lettuce vacuum osmotic dehydration are the temperature of 28°C, the slice thickness of 2 mm, sucrose concentration of 47%, the vacuum degree of 22 kPa, and the water loss rate and solid gain rate are 72.16% and 11.82%, respectively.